IMPLEMENTATION OF STRENGTHENING LITERACY CULTURE IN PJOK LEARNING FOR PJOK TEACHERS IN DOBO CITY, ARU ISLANDS - Tomasoa, Yellia (JUARA : Jurnal Olahraga, 2025)
The objectives of this study are: 1) to find out the implementation of strengthening literacy culture in PJOK learning in junior high school physical education teachers in Dobo Aru Islands, 2) to find out how teachers implement literacy culture in the learning process and in the lesson plan device. The subjects in this study were 25 PE teachers who were divided into several private and public junior high schools in the Aru Islands district. This research is an experimental study using a quantitative descriptive approach with a survey method, the instrument in this study for data collection using a questionnaire. Based on the results of research and data analysis shows that: 1) in the process of implementing learning literacy implementation is in the moderate category, 2) in the implementation of the learning process teachers have several obstacles in implementing a culture of literacy so that implementation in the learning process is less than optimal both in the learning process from opening, implementation to evaluation even in learning tools teachers do not understand and pour in lesson plans.